The Gates of the Alamo : A Novel - Harrigan, Stephen, 1948- (New York : Penguin, 2001)
A full-scale fictional chronicle centered around the fall of the Alamo bristles with historical figures, including Jim Bowie, Santa Anna, and Davy Crockett, among others, as it provides a dramatic re-creation of an event that shaped the history and identity of Texas.
Keywords: Sieges -- Fiction; Alamo (San Antonio, Tex.) -- Siege, 1836; Fiction; Texas -- History -- Revolution, 1835-1836; Fiction; Historical fiction